2022
DOI: 10.3390/molecules27123851
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics of the SARS-CoV-2 Spike Protein: A 2-Year Retrospective Analysis of SARS-CoV-2 Variants (from Alpha to Omicron) Reveals an Early Divergence between Conserved and Variable Epitopes

Abstract: We analyzed the epitope evolution of the spike protein in 1,860,489 SARS-CoV-2 genomes. The structural dynamics of these epitopes was determined by molecular modeling approaches. The D614G mutation, selected in the first months of the pandemic, is still present in currently circulating SARS-CoV-2 strains. This mutation facilitates the conformational change leading to the demasking of the ACE2 binding domain. D614G also abrogated the binding of facilitating antibodies to a linear epitope common to SARS-CoV-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…As a matter of fact, SARS-CoV-2 cellular entry, which is effective thanks to spike protein and ACE2 receptor, can be dramatically changed by a single different nucleotide, the latter changing the entire 3D conformation of the target to its receptor 33 . Moreover, not only can cell biologists now predict the conformational structure of a nucleotide in the spike domain as a result of mutations, but also the viral target-cell receptor affinity resulting from those modifications 34 , which remains extremely sensitive as studies revealed a particular links between Sars-Cov-2 celerity of cellular entry and clinical severity 35 . We strongly encourage teams to involve quasi-species analysis on variant of concern massive surveillance, as we could keep one step ahead fill our quiver with another arrow.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, SARS-CoV-2 cellular entry, which is effective thanks to spike protein and ACE2 receptor, can be dramatically changed by a single different nucleotide, the latter changing the entire 3D conformation of the target to its receptor 33 . Moreover, not only can cell biologists now predict the conformational structure of a nucleotide in the spike domain as a result of mutations, but also the viral target-cell receptor affinity resulting from those modifications 34 , which remains extremely sensitive as studies revealed a particular links between Sars-Cov-2 celerity of cellular entry and clinical severity 35 . We strongly encourage teams to involve quasi-species analysis on variant of concern massive surveillance, as we could keep one step ahead fill our quiver with another arrow.…”
Section: Discussionmentioning
confidence: 99%
“…ADE of coronaviruses can be promoted by antibodies to the spike (S) glycoprotein. This observation was done for SARS-CoV-1 ( 59 , 102 , 157 ) and SARS-CoV-2 ( 127 , 158 ).…”
Section: Mainmentioning
confidence: 99%
“…Recent studies on spike protein interactions with monoclonal antibody 4A8 suggests that epitope located within the N- terminal domain of spike is specific site for its binding [7] , [35] . In SARS-CoV-2 mutations, particularly Delta and Omicron, the primary neutralizing epitope of the N-terminal domain (NTD) of the spike protein displayed substantial structural diversity [21] . This epitope is found on the NTD's flat surface, a significant electropositive region that interacts to host cells' electronegatively charged lipid rafts [14] .…”
Section: Introductionmentioning
confidence: 99%